Analysis of Regional Asset Management and Its Impact on Public Services at BPKAD Nabire Regency - Manan, Budy; Mallisa, Mika; Gunadi , Hendrik (Riviera Publishing, 2025)
This study aims to analyze regional asset management and its impact on public services in BPKAD Nabire Regency. This type of research is qualitative with primary and secondary data sources. Data collection was carried out through observation, interviews with 4 BPKAD employees and 2 local communities, as well as documentation. The data analysis method uses qualitative descriptive analysis with the Spradley approach, which includes data collection, field recording, theme identification, and conclusion drawn. The results of the study show that the management of regional assets in BPKAD Nabire Regency through the stages of inventory, assessment, maintenance, reporting, and supervision seeks to improve the efficiency and effectiveness of public services. Despite good management efforts, constraints such as lack of human resources, technological limitations, minimal budgets, lack of transparency, and regulatory challenges hinder the effectiveness of asset management and the quality of public services. In conclusion, to improve the management of regional assets more effectively, improvements are needed in the capacity of human resources, information technology, budget, as well as transparency and accountability. With these steps, it is hoped that it can improve public services and have a positive impact on the people of Nabire Regency.